Manajemen Modal Kerja Dan Dampaknya Terhadap Nilai Perusahaan Dengan Corporate Governance Sebagai Variabel Pemoderasi - Setyanto, Adrianus Dhimas; Permatasari, Ika (AKRUAL: Jurnal Akuntansi, 2014)
Abstract This study aims to determine the effect of working capital management on firm value. Corporate governance is used as a moderating variable in this study to explore the role of corporate governance in the relationship between working capital management with corporate values. Program participants of Corporate Governance Perception Index (CGPI) are used as a sample during the period from 2003 to 2011 and listed on the Indonesian Stock Exchange (IDX). We were using simple linear regression and the testing of moderating effects were calculated by Moderated Regression Analysis (MRA). The results showed that the working capital management has an influence on the value of the firm. However, corporate governance variables failed to moderate the relationship between working capital management and enterprise value. It shows that companies and investors in the market still lack concern for the program response and Corporate Governance Perception Index (CGPI) as an assessment of the application of the principles of corporate governance that has been done by the company . Keywords: Working Capital Management, Cash Conversion Cycle, Corporate Governance, Firm Values